TEACHING WRITING BY USING ROLL SENTENCES TO SIXTH GRADE STUDENTS OF ELEMENTARY SCHOOL - Desi Ratnasari; An Fauzia Rozani Sy. (Journal of English Language Teaching, 2013)
This article discuss about technique in teaching writing to elementary school students. The technique is roll sentences, roll sentences can develop the students cognitive but also affective, and psychomotor, because this media can make the students more creative. Roll sentences allow children to manipulate sentences pattern. ABSTRAK Artikel ini membahas tentang sebuah teknik dalam mengajar writing pada anak sekolah dasar (SD) teknik yang digunakan adalah roll sentences. Roll sentences dapat membangun perkembangan kognitif,affektif, dan psikomotor anak, karena media ini membuat lebih aktif dan kreatif serta mereka bisa belajar dan bermain. Dalam roll sentences anak dapat menulis kalimat yang benar dalam variasi yang baru. Kata kunci: Roll sentences, Teaching writing, teaching for elementary school.